The Integration of Islamic Noble Characters and Sundanese Local Wisdom to Realize Modernization of Islamic Education - Hidayat, Yusuf; Indriana, Nina; Herniawati, Ani; Hambali, Adang; Basri, Hasan (Journal Corner of Education, Linguistics, and Literature, 2024)
Education in Islam has three basic concepts consisting of Al-Tarbiyah, Al-Ta’dib, and Al-Ta’lim. The three basic concepts has the main goal to achieve ‘Insan Kamil’. This article aims to identify the integration of Islamic noble characters and Sundanese local wisdom to realize modernization of Islamic education. This study employs qualitative method under descriptive approach. The findings assert that Islamic noble characters framed in the acronym of FAST which is described as Fatonah (intelligent), Amanah (trustworthy), Sidik (honest), and Tablig (the person who delivers the mandate). Meanwhile the Sundanese local wisdom framed in the term of Catur-Sila which is described as Silih Asih (loving each other), Silih Asah (educating each other), Silih Asuh (giving knowledge each other, or teaching each other, or educating each other), and Silih Wawangi (making proud each other). In the context of technology 4.0 era, the integration of Islamic noble characters and Sundanese local wisdom is expected to realize modernization of Islamic education at which every Moslem is able to learn Islam in modern ways which is not only having “Insan Kamil”, but also having 4Cs 21st century skills, i.e.: creative thinking, critical thinking & problem solving, communication, and collaboration.